TRANSLATION TECHNIQUES OF ARABIC PHRASES IN THE POETRY OF HAKADZÄ€ AKTUBÅª TÄ€RÄªKH AL-NISÄ€ BY NIZAR QABBANI / TEKNIK TERJEMAHAN FRASA BAHASA ARAB DALAM PUISI HAKADZÄ€ AKTUBÅª TÄ€RÄªKH AL-NISÄ€ KARYA NIZAR QABBANI - Iqbal Mubarok; Yoyo Yoyo (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to evaluate the quality and the techniques of the Indonesian translation of Arabic phrases from Nizar Qabbani's poetry HakadzÄ AktubÅ« TÄrÄ«kh al-NisÄ. This research uses a descriptive analytic method, and the data sources are all Arabic phrases found in Nizar Qabbani's important poem, HakadzÄ AktubÅ« TÄrÄ«kh al-NisÄ. According to the study's findings, HakadzÄ AktubÅ« TÄrÄ«kh al-NisÄ poetry has eight different types of Arabic phrases: idhafy, bayani, athfi, maushuli, zharfy, mazjiy, adadi, and isnadi phrases. This translation makes use of the following eight methods: transference, naturalization, equivalent functional, descriptive equivalent, synonymy, loan translation, modulation, reduction, and expansion. The functional matching, reduction, and expansion procedures are a few that use source language. On the other hand, transfer, naturalization, descriptive matching, synonyms, borrowing, and modulation techniques, tend to favor target language. Based on translation techniques, six Arabic phrases tend to translate based on the source language and the other six tend to translate depending on the target language. It suggests that the translator is more likely to translate certain phrases based on its context.